Eco-Creative Hub Model as The Key to Integrating Creativity and Sustainability - Moh. Khusaini; Firdaus Finuliyah; Alfi Muflikhah Lestari (Universitas Pendidikan Indonesia (UPI), 2023)
Islamic boarding school is essential to developing business in the creative economy with the best quality human resources. This study aims to analyze the potential of Islamic boarding schools to develop creative products with sustainability, with the SWOT analysis. The sample is an eco-creative hub model as a solution to integrate creativity and sustainability with qualitative descriptive analysis. The creative hubs can be facilities to produce creative economy products, collaborate with the creative economy actors, and accelerate innovation. The creative hub model is not only about creativity but also about developing products with sustainability. The development of environmentally friendly products starts with packaging. Institutionally, the government encourages the preservation of the environment.